2013
DOI: 10.14507/epaa.v21n61.2013
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the inclusion imperative: an urban school district’s responses

Abstract: Over the past forty years, schools across the United States have become more inclusive for students with disabilities. However, in many high-poverty urban school districts, a disproportionate number of minority children with disabilities are segregated from their nondisabled peers. This article presents findings from a qualitative case study of one urban school district implementing special education-related inclusion reform over the course of four years. The district had a history of segregating students and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 50 publications
0
32
0
1
Order By: Relevance
“…1 The origins of these failures are related to the intersection of raceand class-based discrimination that culminates with a student being inappropriately identified as having a disability and/or placed in a more restrictive than necessary educational placement. District failures often stem from a lack of funding, training, and inequitable special-education structures that may or may not be due to deficit perspectives held by policymakers and educators (DeMatthews & Mawhinney, 2013;Harry & Klingner, 2006).…”
Section: Special Education and Disproportionalitymentioning
confidence: 99%
“…1 The origins of these failures are related to the intersection of raceand class-based discrimination that culminates with a student being inappropriately identified as having a disability and/or placed in a more restrictive than necessary educational placement. District failures often stem from a lack of funding, training, and inequitable special-education structures that may or may not be due to deficit perspectives held by policymakers and educators (DeMatthews & Mawhinney, 2013;Harry & Klingner, 2006).…”
Section: Special Education and Disproportionalitymentioning
confidence: 99%
“…La unidad de análisis privilegiada es la escuela como comunidad y sus actores presentes o futuros, como factores de la inclusión escolar. Las investigaciones se centran en el análisis del sistema escolar (Blanco, 2006), en estudios de casos de escuelas o de aulas (Ainscow, 2000;DeMatthews y Mawhinney, 2013;Fernández, 2013) y de representaciones del personal docente y del estudiantado de pedagogía (Bhopal y Rhamie, 2014;Garnique-Castro y Gutiérrez-Vidrio, 2011;Sánchez, Díaz, Sanhueza y Friz, 2008). Por lo contrario, el concepto de inclusión/exclusión social cuestiona el modelo democrático en su conjunto y sus consecuencias en el sistema escolar.…”
Section: Dos Concepciones De La Democracia Que Impactan El Nivel De Aunclassified
“…Notably, the school district being studied did not provide ample training or financial support to the schools that were expected to teach an expanded number of students with disabilities due to a change in policy (DeMathews & Mawhinney, 2013). Likewise, many principals reported that they did not support the district's approach to shifting towards more inclusion, and admitted to not following the district's mandate when possible (DeMathews & Mawhinney, 2013).…”
Section: Research-based Targeted Small Group Interventionsmentioning
confidence: 99%
“…Notably, the school district being studied did not provide ample training or financial support to the schools that were expected to teach an expanded number of students with disabilities due to a change in policy (DeMathews & Mawhinney, 2013). Likewise, many principals reported that they did not support the district's approach to shifting towards more inclusion, and admitted to not following the district's mandate when possible (DeMathews & Mawhinney, 2013). Not only does this echo the importance of administrative support raised by other studies, but it also raises questions about the true equity and the quality of instruction that was provided to special education students as this district shifted towards inclusion practices (DeMathews & Mawhinney, 2013).…”
Section: Research-based Targeted Small Group Interventionsmentioning
confidence: 99%
See 1 more Smart Citation